AFTER AMIN: Hijab in Egyptian Feminists Exegesis - Nur Fadiah Anisah; Ahmad Fauzi; Luthfi Raziq (Jurnal Studi Qur'an dan Tafsir, 2023)
Abstract The statement says that the hijab was an obstacle to women's development during colonialism in Egypt sparked a long discussion about the wearing of the hijab at that time, especially after Qasim Amin conveyed it in his book entitled Tahrīr al-Mar'ah (1899). On the other hand, the hijab also paved the way for the emergence of feminist discourse among Egyptian society. This article discusses the hijab discourse in interpretation (tafsīr) in Egypt after the controversy caused by the publication of Qasim Amin's book. This research shows that there are two conflicting tendencies of thinking about women, especially in the wearing of hijab. The first group thinks that the hijab is a barrier to women's development. While the second group considers the hijab is not a determining factor for women's progress. This tendency has genealogical roots to imperialism in Egypt. Using Miriam Cooke's theory of feminism which does not only refer to feminist actions and activism, but also thoughts and seeks to change perceptions of women's social roles and responsibilities, this article analyse at how the hijab discourse in two interpretations published after Tahrīr al-Mar'ah, each written by an Egyptian feminist woman. Focusing on two tafsir, namely al-Sufūr wa al-Hijāb written by Nazirah Zainuddin (1928) and Nazarāt fī Kitābillah written by Zaynab Ghazali (1994), this article elaborates on the verses of the hijab which are interpreted in these two books and sees that – to borrow Amina Wadud's term – prior text cannot be separated from the mufassir. This article concludes that the interpretation carried out by the two women bring the ideology of the feminist groups of the two interpreters, namely the Egyptian Feminist Union (EFU) and the Muslim Ladies Association (MLA). In a broader scope, this also cannot be separated from the history of British imperialism in Egypt, along with the discourse of feminism brought by the imperialists. Keywords: After Amin, Hijab, Feminist-Interpreter